Magnetic hybrid support for ultrasound-assisted magnetic solid-phase extraction of polycyclic aromatic hydrocarbons from produced water - de Barros Caetano, Vinícius Crispim Lima; da Costa Cunha, Graziele; Oliveira, Rhayza Victoria Matos; da Rosa Alexandre, Marcelo; Romão, Luciane Pimenta Cruz [UNESP] (Elsevier, 2019)
This work describes the synthesis of two hybrid organic-inorganic supports with magnetic properties, using water with a high content of natural organic matter (NOM) as solvent and to compose the organic phase. The materials were used in the ultrasound-assisted magnetic solid-phase extraction (UAMSPE) and magnetic dispersive solid-phase extraction (MdSPE) of five polycyclic aromatic hydrocarbons (PAHs) from produced water (PW). The best extraction conditions were achieved using UAMSPE with 20.0 mg of the adsorbent, total extraction time of 5 min, and 10 mL of ethyl acetate as extractant. The linear range, limit of detection (LOD), limit of quantification (LOQ), correlation coefficient (r), and relative standard deviation (RSD) could reach 0.500–100 μg L −1 , 0.010–0.020 μg L −1 (based on S/N = 3), 0.03–0,060 (based on S/N = 3), 0.9943, and 6.7% (50 μg L −1 ) respectively. Upon optimization, the analysis of two PW samples from different wells found PAHs concentrations in the ranges 0.6–1.7 μg L −1 (sample APP1) and 0.5–1.6 μg L −1 (sample APP2). The method was successfully applied to the determination of PAHs in produced water.
Keywords: Magnetic dispersive solid-phase extraction; Organic-inorganic hybrid support; Polycyclic aromatic hydrocarbons; Produced water